Perbedaan Kemampuan Analisis Melalui Model Pembelajaran Kooperatif Tipe Pair Check dengan Make a Match - Rendika Vhalery; Vella Anggresta (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
One of the cognitive domain elements in analysis ability is the ability to think to solve a problem. One way to solve this problem is by using the cooperative learning model of pair-check and "make-a-match." The research objective was (1) to determine whether there was an effect of the type of cooperative learning model of pair-check on students 'analytical skills, (2) to determine whether there was an effect of the cooperative learning model of make-a-match on students' analytical skills, and (3) whether there was a difference in the analytical ability through the learning model cooperative type of pair-check and make-a-match. This research was experimental and comparative research. The population in this study was students of Indraprasta University, which consisted of 2 classes. The techniques of data collection in this study was through a questionnaire used to obtain the results of the analytical skills, observation to observe the use of the cooperative learning model of pair-check and make-a-match, and documentation to obtain direct results (Midterm test and Final Test values). The research implementation stage is divided into three parts: the initial implementation, the core implementation, and the final implementation. The results showed that there was an effect of the type of cooperative learning model of pair-check on students 'analytical abilities, there was an influence of the type of cooperative learning model of make-a-match on students' analytical skills, and there was no difference in analytical skills through the cooperative learning model type check and make-a-match.